Model test of monopile-type offshore wind turbine under breaking waves - Zhang, Songhao; Shi, Wei; Zhou, Lin; Zhang, Lixian; Michailides, Constantine (My University, 2020)
This paper presents results of a hydrodynamic model test of a monopile modeling the NREL 5 MW offshore wind turbine. This paper mainly introduces the test process of the monopile offshore wind turbine under the action of shallow water breaking waves and provides an analysis of the relevant test data. This experiment was carried out in the State Key Laboratory of coastal and offshore Engineering department of the Dalian University of Technology. The monopile model used in the experiment was the NREL 5 MW offshore wind turbine on a 1:80, scale. The physical model is rigid and made of steel. Breaking waves were examined. The wave run-up measurements of seven points are presented, and the experimental data are further processed and analyzed.
Keywords: Breaking waves; Coupled analysis; Dynamic response; Offshore wind energy